New giant H II regions in the southern sky - Firpo, Verónica (2005)
We present results of a search for giant H II regions in southern galaxies. Using high-resolution spectra, obtained with the Magellan Inamori Kyocera Echelle (MIKE) at the Las Campanas Magellan II telescope, we were able to resolve the emission-line profiles and determine the intrinsic velocity dispersion of the ionized gas. Out of four observed regions, selected from previous CCD narrow-band photometry, we detected three H II regions showing supersonic velocity dispersion, characteristic of giant H II regions, and their location in diagnostic diagrams suggests that a powerful starburst is the source of ionization energy.